SISTEM PORTAL INFORMASI KAMPUS UNISBANK BERBASIS APLIKASI MOBILE ANDROID (Information Technology and Telematics, 2012)
Along with the rapid development of technology, especially computer-based information technologies. Today more people want a simple electronic media and can be taken anywhere for their activities, such Tablet, Hp and others. In order to make it easier for students to access information. So in this study were made through mobile-based applications by developing the Android operating system. To support this Portal System Application necessary supporting components such as hardware, software, and brainware which will operate the Campus Information System Application Portal Unisbank. In designing this author Portal System Applications using the Android SDK and Eclipse Indigo as the Android-based software development environment. The conclusion that the author is with the implementation of this system is expected to be all the obstacles that arise when students access information, so the user can directly know the information and facilities are made ​​accessible directly using smartphone devices. The advice given author is an application portal system that made ​​it more interesting to be designed and developed according to the needs again in the future, and feature enhancements of existing facilities on campus Unisbank. KeywordsSyistem Portal Information, Campus Unisbank, Based Android Mobile Application.